2008
DOI: 10.1128/iai.00843-08
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio choleraeFlagellins Induce Toll-Like Receptor 5-Mediated Interleukin-8 Production through Mitogen-Activated Protein Kinase and NF-κB Activation

Abstract: The gram-negative bacterium Vibrio cholerae causes cholera, an acute diarrheal disease characterized by voluminous rice water stools and rapid dehydration. V. cholerae produces an ADP-ribosylating enterotoxin called cholera toxin (CT), encoded by ctxA and ctxB, that activates the host cell enzyme adenylate cyclase, resulting in profuse diarrhea in humans (15). The preeminence of CT as a major virulence factor of cholera was confirmed in volunteer studies, making this toxin a prime target in the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 59 publications
(63 reference statements)
3
60
0
Order By: Relevance
“…Flagellins have been found to interact with TLR5 and to trigger MyD88-and NF-κB-dependent transcription of proinflammatory cytokines (19). Notably, all five V. cholerae flagellins, which can be secreted independently of flagellum filament assembly, contain the amino acid motif that stimulates TLR5, and purified V. cholerae flagellins were found to elicit TLR5-dependent IL-8 secretion from T84 cells (10). In addition, flagellins have been shown to activate the NLRC4 inflammasome, promoting IL-1β maturation and secretion (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flagellins have been found to interact with TLR5 and to trigger MyD88-and NF-κB-dependent transcription of proinflammatory cytokines (19). Notably, all five V. cholerae flagellins, which can be secreted independently of flagellum filament assembly, contain the amino acid motif that stimulates TLR5, and purified V. cholerae flagellins were found to elicit TLR5-dependent IL-8 secretion from T84 cells (10). In addition, flagellins have been shown to activate the NLRC4 inflammasome, promoting IL-1β maturation and secretion (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of these factors might be potentiated by close contact between the bacteria and the epithelium. Finally, recent work using tissue-culture models has led to the hypothesis that the five V. cholerae flagellins, which have been demonstrated to activate the Toll-like receptor 5 (TLR5) signaling pathway, could lead directly to reactogenic diarrhea by stimulating production of proinflammatory cytokines in the intestine (10,11). Detection of lactoferrin and fecal leukocytes in the stools of volunteers with reactogenic diarrhea (12,13) supports the idea that intestinal inflammation is associated with vaccine reactogenicity.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…These studies correlate with clinical observations in which naturally occurring "nontoxigenic" V. cholerae O1 strains that have not acquired the CTX⌽ prophage induce diarrhea that is more inflammatory (5,33). In an infant rabbit model of infection, this diarrhea has been specifically linked to expression of flagellin that may be functioning by increasing inflammatory signaling through TLR5 (20,46,47). Studies using lung infection in mice have also linked proinflammatory signaling from CT-negative strains to LPS-dependent signaling through TLR4 (18), whereas lipoprotein has been shown in vitro to stimulate inflammation via TLR1/TLR2 (16,25).…”
mentioning
confidence: 99%
“…We reported that motility and adherence to intestinal epithelial cells were the triggering factors contributing to IL-8 expression by V. cholerae [13]. Vibrio cholerae flagellins and purified flagella were found to induce IL-8 secretion in vitro [15,16]. Vibrio cholerae flagellins, regardless of whether the proteins were assembled into a flagellum or the flagellum was functional could also elicit IL-8 in vivo [17].…”
Section: Introductionmentioning
confidence: 99%